Etomidate activates epileptic high frequency oscillations - Rampp, Stefan; Heers, M.; Schoenherr, M.; Schmitt, F. C.; Hopfengaertner, R.; Stefan, Hermann; et al. (Clinical Neurophysiology, 2014)
The short acting anesthetic etomidate has been shown to provoke epileptic spikes and rarely seizures. Influence of etomidate on the occurrence of epileptic HFO (high frequency oscillations) however is unknown. An HFO inducing effect of etomidate would allow further validation of the substance as a provocation measure in presurgical evaluation as well as provide insights into the common mechanisms of HFO, spike and seizure generation.We retrospectively analyzed EEG data from four patients who underwent etomidate activation during invasive video-EEG monitoring with subdural strip electrodes. Spikes were manually selected in raw data, HFO in band pass filtered data (80-250Hz). Rate and spatial distribution of HFO and spikes in three segments were compared: immediately after etomidate administration, as well as during slow wave sleep and while awake.Rates of HFO and spikes increased significantly after etomidate administration: Overall average rates of spikes were 9.7/min during sleep, 10/min while awake and 61.4/min after etomidate. Average HFO rates were 9.5/min during sleep, 8.3/min while awake and 24.4/min after etomidate (p<0.001, non-parametric ANOVA). Spatial distributions of HFO and spikes after administration of etomidate were consistent with the seizure onset zone (SOZ) and area of resection when available (SOZ: two patients; resection: one patient; no information: one patient). Except for spurious events, no additional HFO and spike foci were seen with activation.Etomidate administration activates spikes and HFO. Spatial distributions do not extend beyond electrodes showing spikes and HFO without Etomidate and seem consistent with the epileptic network.Etomidate activation is a safe procedure to provoke not only epileptic spikes but also HFO, which were shown to have a high specificity for the SO
EVALuna2:16662